Performance analysis of a modified pneumatic separator for cowpeas (2007)
In this work, modifications have been done on a prototype pneumatic separator to improve its efficiency. The effects of the modifications were studied by carrying out performance test analyses on the two blowers and reciprocating sieve mechanism which make up the critical components of the separating machine. The variations in the feed weights of the sieve were analyzed to determine the best and most effective screening process. Also, the best and least tilt angles of the blowers were considered to determine the best and least blowing processes to clean the beans. The results of analyses showed that for a feed weight of 3.0kg the sieving process attained its best efficiency of 50.2%. The maximum efficiency of 79.2% for the first pneumatic separator was obtained at a tilt angle of 30°, while a maximum of 77.7% was obtained for the second separator at 0° tilt angle. An overall efficiency of 77% was estimated for the modified pneumatic separator.